The diagnostic yield of computerised tomography in human immunodeficiency virus (HIV) positive psychiatric patients at a tertiary hospital in the Western Cape - Berwers, Juan (Department of Psychiatry and Mental Health, 2018)
Background. HIV infection increases the risk for mental illness. Neuroimaging is an important part of the diagnostic workup in HIV+ psychiatric patients; CT is the primary neuroimaging modality available in resource limited settings. Despite advances in neuroimaging no clear guidelines exist for the use of CT in psychiatric settings. Objective. To determine the diagnostic yield of CT brain (CTB) scans in HIV+ psychiatric patients and to describe these abnormalities as well as demographic and clinical variables associated with abnormal CT scans. Methods. A retrospective study was conducted at the Department of Psychiatry and Mental illness at Groote Schuur Hospital, Cape Town, South Africa. Clinical and radiological data for HIV+ psychiatric patients who received a CTB scan during admission were analysed for the period January 2013 - June 2015. Results. A total of 65 patients met the inclusion criteria. The mean age of the participants in this study was 36.2 years (range 18 - 64). The most common presenting psychiatric symptoms were psychosis (81.54%), cognitive deficits (72.41%) and mood symptoms (69.23%). CT scans results consisted of 29 (44.62%) normal scans and 36 (55.38%) abnormal scans. Atrophy was the most common (72%) radiological finding in abnormal CT scans. No associations were found between current proposed CT guidelines in psychiatric patients, although a history of previous traumatic brain injury (TBI) approached significance (p = 0.054). There was a significant correlation between abnormal CT scans and past or current substance use (X² = 5.9508 P = .015). Abnormal CT findings increased with the Centers for Disease Control and Prevention (CDC) HIV immunological stage progression. The management of 9 patients changed; 7 of these CT scans were abnormal. Conclusion. In this study of CTB scans in HIV+ psychiatric inpatients, previously suggested criteria proposed in guidelines for imaging were not associated with significantly higher rates of abnormal CT findings. Current or previous substance use correlated with significant higher rates of abnormal CT findings. Due to the high yield of abnormal CT scans in this study, it is suggested that HIV+ psychiatric inpatients with previous or current substance use, a history of TBI or HIV immunological stages B or C, are considered for imaging. It is recommended that further studies with larger sample sizes, consisting of inpatient and outpatient populations, with control groups be conducted to investigate current or previous substance use as an indication in guidelines for CTB scan in HIV+ psychiatric patients.